Pengaruh Lingkungan Belajar Terhadap Hasil Belajar Mahasiswa Dalam Matakuliah Akuntansi Pemerintah - Husni Mubarak; Karina Krisnanda (JAS (Jurnal Akuntansi Syariah), 2019)
One of the functions of face-to-face lectures in class is as a transfer of knowledge from lecturer to students. The student learning environment is an external factor that influences student learning outcomes. Government Accounting Course I is a continuation of the Public Sector Accounting course. The purpose of this course is to provide knowledge to students of the Diploma 4 Public Financial Accounting Study Program that focuses on the process of financial recording and reporting to the government. This study was conducted to determine whether there are differences in learning outcomes in Government Accounting courses I between classes A and B. The test instrument used is the non-parametric Mann-Whitney test. The population in this study was 52 students in the fifth semester of Diploma 4 Public Financial Accounting Study Program. The results of this study showed that the learning outcomes or students' abilities in Government Accounting courses I between classes A and class B did not differ. Differences in the learning environment in each class do not affect student learning outcomes.